Influence of granitic aggregates from northeast Brazil on the alkali-aggregate reaction - Gomes Neto,David de Paiva (2014)
The alkali-aggregate reaction (AAR) in concrete structures is a problem that has concerned engineers and researchers for decades. This reaction occurs when silicates in the aggregates react with the alkalis, forming an expanded gel that can cause cracks in the concrete and reduce its lifespan. The aim of this study was to characterize three coarse granitic aggregates employed in concrete production in northeastern Brazil, correlating petrographic analysis with the kinetics of silica dissolution and the evolution of expansions in mortar bars, assisted by SEM/EDS, XRD, and EDX. The presence of grains showing recrystallization into individual microcrystalline quartz subgrains was associated with faster dissolution of silica and greater expansion in mortar bars. Aggregates showing substantial deformation, such as stretched grains of quartz with strong undulatory extinction, experienced slower dissolution, with reaction and expansion occurring over longer periods that could not be detected using accelerated tests with mortar bars.